Preparation and characterization of a core‐shell curing agent for the composite repair prepreg system. Issue 11 (2nd August 2013) - Xing, Suli; Yang, Jinshui; Yin, Changping; Zeng, Jingcheng; Xiao, Jiayu
<x xml:space="preserve">Abstract</x> A core‐shell curing agent, in which E‐44 epoxy resin modified 4, 4'‐diaminodiphenylmethane (M‐DDM) is used as the core material and toluene‐2, 4‐diisocyanate (TDI) as the shell monomer, was prepared by an in situ interfacial polymerization technique to prolong the shelf life of the composite repair prepreg system. The shell was formed on the surface of the M‐DDM particles by the polyaddition of M‐DDM and TDI monomers, and the mean thickness of the shell is about 100 nm. The core‐shell particles showed an irregular sphere‐like shape with a narrow size distribution, and the mean size of the core‐shell particles was about 2.54 μm. The core‐shell curing agent exhibited an excellent curing ability and a promising storage property of about 6 months, which can be applied in the field of the prepreg system for the rapid composite repair of the damaged structures. POLYM. COMPOS., 34:1892–1900, 2013. © 2013 Society of Plastics Engineers